Evaluation of the contribution of National Housing Fund scheme towards housing delivery in Nigeria - Adedokun, O.A.; Akinradewo, F.O.; Adegoke, J.O.; Abiola-falemu, J.O. (Penerbit UKM, 2012)
One of the three most important basic needs of mankind which has not been adequate for the citizenry right from the independence in 1960 till date is Housing. Finance has been fingered as one of the predicaments towards its actualization because housing provision requires huge capital outlay. The National Housing Fund (NHF) scheme was considered relative to the number of contributors, accessibility of the fund when required and how it has affected the provision of housing in Nigeria. Data for this work were obtained from the Federal Mortgage Bank of Nigeria (FMBN) which is the apex bank for mortgage institutions. The study revealed that few mortgagors have benefitted from the scheme,funds are locked up without disbursing adequate amount to the contributors as there is wide gap between the amount that mortgagors actually applied for and the amount so approved for the provision of housing in Nigeria. The paper recommended that contributors should be allowed to benefit from NHF scheme, while funds locked up should be adequately disbursed to the loan applicants by ensuring that there is reduction in the wide margin between amount applied for and the amount so approved to allow for effective utilization of the fund.